Learning beliefs of seven adult Malay Muslim learners in non-formal learning environments - Abdul Wahab, Rohaya (2013)
This research aimed to identify and understand the learning beliefs among adult Malay Muslim learners participating in non-formal Islamic learning environments. In addition, it explored how far these learning beliefs are transformative in nature and in what ways these learning beliefs of adult Muslim learners fit Islamic views and perspectives of learning and education. This study focused on learning as interpreted and understood from the perspective of the learners themselves, from the general as well as holistic perspective based on their learning experiences and learning processes. Utilizing the phenomenological qualitative research method, the sample for this study were seven adult learners who are in the middle adulthood and above,in the 40 year old and above age group. They participated voluntarily and regularly in at least two non-formal religious learning programs. Data were mainly collected using in-depth interviews, informal conversations and email interviews, and were analysed by thematic analysis. The findings of this study show that the meanings attached to the informants’ learning beliefs were common among them and that these beliefs were hierarchical in nature, ranging from simple to complex. At the simplest level, learning was considered as merely to be acquiring and gaining knowledge; whilst at a more complex level, learning became internalized and practised by the informants; and at the highest end, learning was conceived as internalizing and changing not just one’s physical perspective but also one’s worldview in relation to God. This study moreover revealed that learning beliefs (in these non-formal learning programs) were more transformative in nature, involving changes in applying practical knowledge, heightened religious consciousness, enhancing personal development, and seeking spiritual pleasure. In addition, the acknowledged motivation for holding learning beliefs from the Islamic perspective was based on three inter-related reasons –temporal, temporal as well as moral, and Hereafter and Godly reasons; with the last reason being the most dominant. Therefore, these beliefs among adult Malay Muslim Learners were shown to be spiritualistic in nature and consequently, all the themes were tied strongly to eternal and Godly reasons. The main conclusions are all these different themes converged into a singular spiritual essence at the summit, and thus learning in non formal situations is deeply connected to the essences and perspectives of spirituality; the key to understanding adult learning is to understand the adult learners themselves; adults participate and seek educational activities that relate to personal growth and development; and it is particularly important to look at cultural and religious contexts of the learners and the learning environment to understand better how their beliefs and experiences shape the learners’ beliefs on learning. Implications of the study are that educators need to consider the significance and relevance of culture, religion, and spiritual essences in adult learning, to promote critical thinking in non-formal learning among adults, and to consider the nature of learning as lifelong, transformative and experiential. These are the challenges to the practice of adult education.